Lung function improvement and airways inflammation reduction in asthmatic children after a rehabilitation program at moderate altitude. Issue 8 (2nd November 2017) - Bersuch, Eugen; Gräf, Florian; Renner, Ellen D.; Jung, Andreas; Traidl‐Hoffmann, Claudia; Lauener, Roger; Roduit, Caroline
Abstract: Background: Rehabilitational programs at moderate altitude (1500‐2500 m) showed improvement of lung function and reduction in airways inflammation in asthmatic adults. Allergen avoidance was postulated as the major cause of these improvements. Methods: Spirometries of 344 and fractional exhaled nitric oxide measurements (FeNO) of 124 asthmatic children and adolescents, staying in a rehabilitation hospital in Davos (1590 m) with at least 14 days between admission and discharge, were analyzed in association with atopic sensitization (skin‐prick testing and/or specific IgE), level of asthma control, and inhalative corticosteroid (ICS) dose. Results: Pulmonary conditions improved significantly on average during the sojourn. Uncontrolled asthmatics benefited most with an absolute increase in predicted FEV1, MEF25, and MEF75 of 7.7%, 9.9%, and 12.7%, respectively ( P < .001). FeNO decreased by 36.9 ppb for uncontrolled, by 26.9 ppb for partly controlled, and by 11.8 ppb for controlled asthmatics. In uncontrolled subjects, pulmonary improvement was comparable between patients with and without house dust mites (HDM) sensitization. Pulmonary improvements of pollen‐sensitized patients were not dependent on the season of the sojourn. For the group with constant ICS level, the absolute increase in FEV1 was 4.9% ( P < .001) with a FeNO decreased by 32.7 ppb ( P < .001). When the ICS dose was elevated by one GINA level, the absolute increase in FEV1 was slightly higher (6.6%, P < .001), with a FeNO decrease of 31.4 ppb ( P < .001). Conclusion: Inpatient rehabilitation at moderate altitude improved pulmonary conditions in asthmatic children and adolescents independent of sensitization status to HDM or pollen. A positive effect was also observed in patients without change in medication.